Pentecostalismo e imaginário: rupturas e continuidades na hinologia pentecostal na passagem da modernidade para a pós-modernidade - Peixoto, Esdras Gusmao de Holanda (2008)
This dissertation attempts to investigate the discontinuities and continuities in the theology, mentality and world-vision of Brazilian pentecostals. To that end it has as its special object of study the musical repertoire of the pentecostal communities, evaluating the internal evolution of that which is sung in the worship services and other meetings. Music is the principal means by which the behavior of the faithful is moulded. Since it is a product derived from the surrounding culture, and so not completely controlled by the composer, pentecostal hymnology both reflects and inculcates symbols which direct the universe which its followers inhabit. Gilbert Durand's book, The Theory of the Imaginary, provides the hermeneutical basis for our interpretation of the symbolic as present in the hymn-books both of classic pentecostalism and of post-pentecostalism, and we apply Durand's methodology to the images present in the pentecostal hymns. As to its epistemology, this study is both transdisciplinary and comprehensive, as well as taking into account current sociological trends present in what is known as post-modernity